Simulation research on the force and motion of solid particles in transformer oil under DC voltage. (November 2022) - Meng, Xuan; Guo, Ruochen; Hou, Jiachen; Wang, Haotian; Li, Junhao
Abstract: As the essential equipment in ultra-high voltage direct current transmission systems, converter transformers provide an important role in the stable operation of the power grid. During the long-term operation of converter transformers, the aging and decomposition of the oil-paper insulation cause a great quantity of metal and non-metal solid particles in the transformer oil, which is one of the important reasons for the equipment failure. The solid particles are affected by various forces in transformer oil, among which the Coulomb force dominates their motion characteristics. The charging process of solid particles contacting the electrode is very important. There are many discussions on the charge carried by metal particles after colliding with the electrode, but less research on the Coulomb force of non-metallic particles in the oil. A simulation model is established to calculate the Coulomb force of metal and non-metal particles in the oil, and the moving process of spherical solid particles of different diameters under different voltages is observed. The research shows that for spherical solid particles with the same material, the Coulomb force increases non-linearly with the increase of particle size. For particles with different materials of the same particle size, the Coulomb force experienced by metal particles is relatively large. Therefore, the charge carried by non-metal particles after colliding with the electrode cannot be calculated by the charge calculation method of metal particles. The research is helpful to analyze the force and movement process of particles in oil and provides support for transformer fault diagnosis and insulation structure design.